The concept of acquired knowledge ('ilm al-husuli) : its reformation in the discourse of Muslim scholars - Mohd Amin, Wan Mohd Adam (2011)
This paper examines the concept of acquired knowledge (‘ilm al-ÍuÎËlÊ) in the discourse of Muslim scholars in relation to the reforms made by many Muslim scholars and thinkers such as al-ShÉfi‘Ê (d.204/820), al-GhazÉlÊ (d. 505/1111) and al-DihlawÊ (d.1176/1762). Al-ShÉfi‘Ê contributed much to this field with his classification of knowledge into two categories, ‘ilm al-‘Émmah and ‘ilm al-khÉÎÎah. Al-GhazÉlÊ, who developed ‘ilm al-mu‘Émalah and al-mukÉshafah, suggested a method of revivification (iÍyÉ’) in order to integrate the sciences of acquired knowledge. Al-DihlawÊ developed and classified knowledge into ‘ilm al-ÍuÌËrÊ and al-ÍuÎËlÊ, and suggested the concept of taÏbÊq in reforming acquired knowledge. Their discussions on the reformation of acquired knowledge have paved the way for modern scholars to derive concepts for the integration of human knowledge.